Local-scale environmental filtering shape plant taxonomic and phylogenetic diversity in an isolated Amazonian tepui (Tepequém table mountain) - Campos, Prímula Viana; Schaefer, Carlos Ernesto G. R.; Pontara, Vanessa; Xavier, Márcio Venícius Barbosa; do Vale Júnior, José Frutuoso; Corrêa, Guilherme Resende; Villa, Pedro Manuel (Evolutionary ecology, 2022)
Understanding how environmental drivers induce changes in plant composition and diversity across evolutionary time can provide important insights into community assembly mechanisms. We evaluated how taxonomic and phylogenetic diversity and structure of plant communities change along a local-scale edaphic and elevational gradient in the Tepequém table mountain, Brazilian Amazon. We selected three phytophysiognomies along the altitudinal gradient: Open Rupestrian Grassland, Shrubby Rupestrian Grassland, and Forest. We compared community composition and taxonomic and phylogenetic diversity between phytophysiognomies, and analysed effects of altitude and soil properties on species richness and phylogenetic metrics using linear mixed-effects models. The highest species richness and phylogenetic diversity were found at a lower elevation for Forest. All standardised phylogenetic metrics were significantly lower in Shrubby Rupestrian Grassland. This phytophysiognomy showed phylogenetic clustering. Forest showed a cluster pattern when only terminal nodes are considered and random dispersion to deep phylogenetic nodes. Open Rupestrian Grassland also showed a random phylogenetic structure. The linear mixed-effects models showed that species richness and different phylogenetic structure metrics were explained by altitude and soil properties. Our study revealed that key plant diversity dimensions (i.e. taxonomic and phylogenetic) are shaped by a local-scale edaphic and elevational gradient on an isolated tepui of Brazilian Amazonian.